Relationship Between Family Affective Function and Smoking Cessation in Adolescents - Sang Ayu Made Adyani; Asya Shalbiah Muamar (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: Adolescents as individuals who are in transition from children to adults experience bio-psycho-socio and spiritual changes. At this time, adolescents are very vulnerable to being affected by negative things from the surrounding environment, one of which is smoking. Besides being influenced by environmental factors and peers, the affective function of the family also affects smoking behavior in adolescents. Objectives: The purpose of this study was to analyze the relationship between affective function and smoking cessation in adolescents in Srengseng Sawah Subdistrict. Methods: This study uses quantitative research methods with cross sectional design. The number of samples is 296 adolescents with the inclusion criteria of adolescent smokers aged 10-24 years and not married and living with their families. Data was collected by filling out a questionnaire. Data were analyzed using chi-square statistical test. Results: The results showed that there was a relationship between family affective function and smoking cessation in adolescents in Srengseng Sawah Subdistrict with a p-value of 0.000 (p <0.05). Conclusion: The results of this study are expected to provide benefits for adolescents to grow determination and increase motivation to quit smoking by increasing positive interactions with parents and avoiding things that cause the urge to smoke.